Analysis of sensorimotor control in people with and without neck pain using inertial sensor technology: study protocol for a 1-year longitudinal prospective observational study. Issue 2 (15th February 2022) - Moggioli, Filippo; Pérez-Fernández, Tomas; Liébana, Sonia; Corredor, Elena Bocos; Armijo-Olivo, Susan; Fernandez-Carnero, Josue; Raya, Rafael; Conde, Pablo; Rodríguez-López, Oscar; Sánchez, Cristina; Martín-Pintado-Zugasti, Aitor
Abstract : Introduction: Neck pain is a very common musculoskeletal disorder associated with high socioeconomic costs derived from work absenteeism and medical expenses. Previous studies have suggested that patients with neck pain of different origins present sensorimotor control impairments compared with the asymptomatic population. However, there is a small number of published studies focusing on these with conflicting results. In addition, the existing methodological limitations highlight the need for more and better quality studies. Moreover, longitudinal studies are necessary to investigate whether changes in pain or disability in individuals with chronic neck pain over time associate with changes in cervical sensorimotor control. Methods and analysis: This is a descriptive, observational, longitudinal, prospective study consecutively enrolling 52 patients with non-specific neck pain and 52 age-matched asymptomatic participants. Intensity of pain, neck disability, duration of symptoms, topography of pain and comorbidities will be registered at baseline. Sensorimotor control variables including active range of motion, movement speed, acceleration, smoothness of motion, head repositioning accuracy and motion coupling patterns will be recorded as primary outcomes by means of inertial sensors during the following tests consecutively performed in two sessions separated by 12 months: (1) kinematics of planar movements, (2) kinematics of the craniocervical flexion movement, (3) kinematics during functional tasks and (4) kinematics of task-oriented neck movements in response to visual targets. Secondary outcomes will include: (1) Regular physical activity levels, (2) Kinesiophobia, (3) Symptoms related to central sensitisation and (4) The usability of the inertial measurement unit sensor technology. Ethics and dissemination: This study was approved by the Research Ethics Committee of CEU San Pablo University (495/21/39). Patients will be recruited after providing written informed consent and they will be able to withdraw their consent at any time. Only the study investigators will have access to the study data. The results will be disseminated through scientific publications, conferences and media. Trial registration number: NCT05032911 .